2019
DOI: 10.21873/anticanres.13836
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Antibiotics on Prognosis of Metastatic Renal Cell Carcinoma in Japanese Patients Treated With Immune Checkpoint Inhibitors

Abstract: Background/Aim: The present study aimed to examine the influence of antibiotics (AB) on the clinical outcomes of Japanese patients treated with immune check point inhibitors (ICIs) for metastatic renal cell carcinoma (RCC) patients. Patients and Methods: A total of 31 patients with metastatic RCC treated with ICIs from November 2016 to April 2019 were retrospectively reviewed and analyzed. Results: Five patients were treated with AB prior to ICIs treatment. Median progression free survival (PFS) of patients tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 19 publications
1
25
0
1
Order By: Relevance
“…25,26 Finally, our results showed that OS was similar in patients treated with inhaled corticosteroids and in those not treated with these drugs, as already described by Li et al 18 Thus, the use of this corticosteroid administration route does not appear to influence the effectiveness of ICIs. 23,[29][30][31][32] ATBs appear to have an indirect negative impact on the ICIs' effectiveness by modifying the composition of gut microbiota. 29,33 However, these results could also be explained by the indication bias -that is, the infection for which the ATB is used -and not the ATB itself.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Finally, our results showed that OS was similar in patients treated with inhaled corticosteroids and in those not treated with these drugs, as already described by Li et al 18 Thus, the use of this corticosteroid administration route does not appear to influence the effectiveness of ICIs. 23,[29][30][31][32] ATBs appear to have an indirect negative impact on the ICIs' effectiveness by modifying the composition of gut microbiota. 29,33 However, these results could also be explained by the indication bias -that is, the infection for which the ATB is used -and not the ATB itself.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,19 Other reports have shown that antibiotic use reduces the clinical efficacy of immunotherapy in patients with metastatic renal cell and non-small-cell lung cancer. 20,21 It has been widely known that human gut microbiota consists of nearly 1000 bacterial species, and metagenome analyses are improving to acquire the functional information regarding these species. 22 Recently, it was reported that gut microbiota richness is strongly associated with defecation patterns, including stool consistency and frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with non‐responders to the immunotherapy, responders had more abundance of bacteria of the Ruminococcaceae family, and Bifidobacterium and Faecalibacterium genera, whereas the microbiota of non‐responding patients was enriched with bacteria of the Bacteroides genus 8,9,19 . Other reports have shown that antibiotic use reduces the clinical efficacy of immunotherapy in patients with metastatic renal cell and non‐small‐cell lung cancer 20,21 …”
Section: Discussionmentioning
confidence: 99%
“…Das heißt, Patienten, die vor oder während einer Immuntherapie mit Checkpoint-Inhibitoren eine Antibiotikatherapie erhielten, zeigten einen insgesamt ungünstigeren Krankheitsverlauf in Bezug auf progressionsfreies Überleben und Gesamtüberleben. Dieser Zusammenhang wurde in weiteren Studien und Meta-Analysen untersucht und bestätigt [18][19][20][21]. Durch die Antibiotikagabe kam es unter anderem zu einem vermehrten Auftreten von Clostridium hathewayi, was insgesamt zu einem schlechteren Outcome führte [22].…”
Section: Nierenzellkarzinom Und Harnblasenkarzinomunclassified